2019
DOI: 10.1073/pnas.1902771116
|View full text |Cite
|
Sign up to set email alerts
|

An R2R3 MYB transcription factor confers brown planthopper resistance by regulating the phenylalanine ammonia-lyase pathway in rice

Abstract: Brown planthopper (BPH) is one of the most destructive insects affecting rice (Oryza sativaL.) production. Phenylalanine ammonia-lyase (PAL) is a key enzyme involved in plant defense against pathogens, but the role of PAL in insect resistance is still poorly understood. Here we show that expression of the majority ofPALsin rice is significantly induced by BPH feeding. Knockdown of OsPALssignificantly reduces BPH resistance, whereas overexpression ofOsPAL8in a susceptible rice cultivar significantly enhances it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(170 citation statements)
references
References 36 publications
5
165
0
Order By: Relevance
“…However, in this study, the Ganoderma species had mostly 1R-MYBs, with no clearly conserved gene structure found. As the dominant 2R-MYBs play central roles in plant-specific processes (Lee & Seo 2019;He et al 2020), it is likely that the dominant 1R-MYBs might play core roles in relevant processes in Ganoderma species.…”
Section: Co-expression Analysis Of G Lucidum Myb Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, the Ganoderma species had mostly 1R-MYBs, with no clearly conserved gene structure found. As the dominant 2R-MYBs play central roles in plant-specific processes (Lee & Seo 2019;He et al 2020), it is likely that the dominant 1R-MYBs might play core roles in relevant processes in Ganoderma species.…”
Section: Co-expression Analysis Of G Lucidum Myb Genesmentioning
confidence: 99%
“…Abundant evidence in plants has confirmed the diverse roles of MYB genes in signal transduction, developmental regulation, biotic and abiotic stress responses, disease resistance, and secondary metabolism regulation Lee & Seo 2019;Qing et al 2019;Wu et al 2019b;He et al 2020;Ohno et al 2020). Similarly, a few studies have shown that MYB genes participate in stress response and developmental regulation in fungi (Valsecchi et al 2017;Wang et al 2018;.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown that JA-and ET-mediated signaling pathways reduce rice resistance to BPH (Lu et al, 2014;Zhou et al, 2009), whereas SA-and H 2 O 2 -mediated pathways increase it (Hu et al, 2016;Wang, 2012). Recently, He et al (2020) found that phenylalanine ammonialyases, which are regulated by an R2R3 MYB transcription factor, OsMYB30, modulate the resistance of rice to BPH by regulating the biosynthesis and accumulation of salicylic acid and lignin. In this study, we also found that exogenously applying H 2 O 2 to WT plants enhances their resistance to BPH at the same levels reached by the ir-rlk2 lines ( Figure S12), confirming the important role of the H 2 O 2 pathway.…”
Section: F I G U R Ementioning
confidence: 99%
“…In our results laccase OsLAC5 was down-regulated in flag leaf and OsLAC4, a microRNA target gene on chromosome 1 was up-regulated in panicle. The PAL genes OsPAL6 and OsPAL8 mediate brown planthopper resistance by controlling lignin biosynthesis and its accumulation in rice 72 . Phenylalanine ammonia-lyase (OsPAL4) on chromosome 2 is associated with broad spectrum disease resistance in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Both expression and sequence analysis indicates that OsPAL2 and OsPAL4 influence grain yield in test hybrid. Thus phenyl propanoid pathway and PAL genes in particular are at centre stage of not only broad spectrum disease 74 , pest resistance 72 and tolerance to abiotic stress 75 but also for increasing grain yield.…”
Section: Discussionmentioning
confidence: 99%